On the relations between grammar and reality: a wittgensteinian study - Mota, Sergio (Analysis. Journal of Philosophical Research, 2020)
In this paper I propose to analyze a reading of the work of Wittgenstein mainly developed by Moyal-Sharrock in which it is claimed that grammar is conditioned by certain facts (i.e. by general facts of nature). Thus, while I agree that grammar is not independent of reality, the relation (and connection) between grammar and reality is not captured, to my mind, by speaking of facts as conditions or determinants. As I will defend in this paper based on authors like Wittgenstein, Nietzsche, Rhees or Feyerabend, reality, which is thought to permeate grammar, is itself, at the same time, permeated by grammar. So this paper has a twofold objective. Primarily, to show that the reading mentioned above is biased and does not adequately express, in my view, what Wittgenstein points out with that connection. Secondly, this connection shows that there are certain ‘facts’ which play a peculiar logical role: they are beyond truth and falsity (which does not mean that these facts must be true). Rather, my aim is to analyze the grammatical role of certain ‘facts’ that are not called into question, but not because they are intrinsically obvious or convincing.